Kontribusi Usaha Kelapa Menjadi Kopra Terhadap Pendapatan Rumah Tangga Petani di Kelurahan Gubukusuma Kecamatan Tidore Utara Kota Tidore Kepulauan - Ilfan Baharuddin; Muhammad Hi. Hasan (Peneliti.net, 2021)
Plantation is the number one business that is mostly cultivated by the people in the Tidore Islands City. With its geographical location and tropical climate, Tidore is one of the cities with good plantation business development, one of which is coconut plantations. The potential of coconut is so good that it can be developed to improve the community's economy. But in reality this is not the case, this happens because the existing potential has not been fully utilized by the community. The drying of coconuts into copra carried out by the Gubukusuma community is still conventional, namely by smoking, of course the results are also different from modern drying which is carried out using a drying machine, the coconut drying system into copra carried out using a machine will produce white copra with high quality. which is better than the smoking system which produces black or gray copra. The problem that is often encountered by coconut farmers is the yield of copra which is considered low by copra buyers in the market, departing from the problem of processing coconuts into copra. for the household income of farmers. The urgency of the research that the researcher wants to convey from this research is that the local government, especially the Tidore Islands City Government, should be able to closely monitor the selling price of copra in the market so that there is no price game by copra buyers.